Taxonomic Observation of Avian Tape Worm Davainea Gunjotinesis n.Sp. from Gallus Gallus Domesticus (Linnaeus) - Pathan*, D.M. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">The present study deals with the taxonomic observation of avian tape worm Davainea gunjotinesis n.sp. collected from intestine of a Gallus gallus domesticus (Linnaeus) at Omerga, Osmanabad district (M.S.), India. The worm comes closer to all the known species of this genus in general topography of organ but differs due to scolex globular, four suckers, rostellar hooks 20-22 in numbers, neck absent, mature proglottids broader than long, testes 55-60 in numbers, cirrus pouch large, oval placed towards the 1/4th anterior margin of the proglottids, genital pores large, oval in shape, marginal and irregularly alternate. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">— Department of Zoology, Shrikrishahavidyalaya, Gunjoti Dist- Osmanabad (M.S.) - 413 606, IndiaÂ Â — Please Cite This Article As: Â D.M. Pathan. 2010. Taxonomic Observation of Avian Tape Worm Davainea Gunjotinesis n.Sp. from Gallus Gallus Domesticus (Linnaeus). J. Ecobiotechnol. 2(6):21-24. Â